Climate Change Impacts on Surface Water Availability & Management of Jordan's Zarqa River Basin Using Soil and Water Assessment Tool (SWAT). - Haddad, Mira; Rahbeh, Michel; Strohmeier, Stefan; Ziadat, Feras M. (2017)
Zarqa River Basin (ZRB) is among Jordan's most important surface water basins, hosting the country's major cities and industry, and providing water for agricultural production within the basin and beyond. ZRB's surface runoff dilutes the treated wastewater of Khirbat As-Samra plant, mainly discharged by Greater Amman's and Zarqa's wastewater, before reaching King Talal Dam and further downstream covering up irrigation water demands of the Jordan Valley. Due to deforestation, intensive agriculture and overgrazing large areas of ZRB became vulnerable to soil erosion and thus land degradation - whereas the eroded sediments of the basin eventually accumulate in King Talal Reservoir and consequently decrease the impoundment's storage capacity. On top of this, the changing climate affects both quantity and the occurrence pattern of rainfall potentially speeding up land degradation and water storage loss of the King Talal Reservoir. A hydrological model was set-up to better understand the spatial pattern of surface water affected by various Soil and Water Conservation interventions within the basin and thus to reflect the landscape's response to 1) actual, as well as 2) future climatic conditions of different rainfall and temperature chaning scenarios; using different Representative Concentration Pathways (RCPs) from the highest available resolution data of the Global Circulation Models (GCMs). This contributes to the assessment future surface water availability - to increase preparedness for the predicted climatic changes and to support the development of mitigation strategies align with the Jordanian water sector management plans.